ANALISIS KESIAPAN SISWA SMK DALAM MEMASUKI DUNIA KERJA DAN MINAT MELANJUTKAN JENJANG PENDIDIKAN PADA MASA PANDEMI COVID-19 - Harisa Rahmah, - (2022)
During the COVID-19 pandemic, vocational students still felt uncertain about continuing their education or entering the world of work, because COVID-19 made the education system all digital. Vocational learning, practicums, industrial practices, and competency tests are less than optimal to equip students to face the world of work. Then, the reduced motivation of students in learning, the declining economy of parents, and a non-conducive school environment affect their interest in continuing education. This study aims to determine: (1) the readiness of vocational students to enter the world of work and (2) the interest of vocational students to continue their education level during this Covid-19 pandemic. The research method applied in this study is qualitative method. Based on the outcome of the discussion: (1) Students are quite ready to face the world of work and realize the importance of being prepared to face the world of work. The factors that influence students' readiness to enter the world of work are: Internal Factors, Willingness, and Self-Motivation of Students and Soft Skills; External Factors, Parents' socio-economic status, Vocational Learning in Schools, Industrial Practice Experience, Competency Test and (2) Students have a high enough interest to continue their education from 10 informants, 8 people expressed their interest in continuing education and students know the importance continue education. The factors that influence student's interest in continuing their education are: Internal factors, academic achievement; External factors are the socio-economic status of parents, and the environment, which consists of the family, school, and community environment.